Implementasi Digital Aplikasi GaweTani di Kawasan Food Estate Lampung Barat sebagai Solusi Ketahanan Pangan: Implementasi Digital Aplikasi GaweTani di Kawasan Food Estate Lampung Barat sebagai Solusi Ketahanan Pangan - Sony Ferbangkara; Martinus; Rizkima Akbar Setiawan; Resty Annisa; Ubaidah (Nemui Nyimah, 2025)
This community service program aims to enhance agricultural efficiency and productivity in the Food Estate area of West Lampung through digital assistance using the GaweTani application. GaweTani is a digital platform designed to help farmers manage their land more efficiently by providing real-time data access related to weather conditions, soil, and market prices. The program was implemented in four stages: preparation of digital infrastructure and area data mapping, development of the GaweTani application, field implementation with training for farmers, and evaluation of the application's impact on productivity and efficiency. Local partners were also involved to assist farmers, ensuring the application is used effectively to maximize harvest yields and improve farmers' welfare. The implementation successfully increased farmers' digital literacy and encouraged the development of sustainable smart agriculture in the area. The application provides integrated management, real-time information access, and technical guidance, which helps farmers make more informed decisions.